Initial vegetative development and early selection of arabica coffee cultivars in a low-altitude region - Filla, Vinícius Augusto [UNESP]; Coelho, Anderson Prates [UNESP]; Terceiro, Matheus Grossi [UNESP]; Morello, Orlando Ferreira [UNESP]; Lemos, Leandro Borges [UNESP] (FapUNIFESP (SciELO), 2023)
The cultivation of Coffea arabica L. in a low-altitude region is a sustainable alternative for diversifying the income of farmers. On account of the variability of available cultivars, the use of indirect selection through initial vegetative development may be an auxiliary tool for identifying the most suitable genotypes for this environment. This study aimed to identify the dwarf Arabica coffee cultivars with better initial development in a low-altitude region and the morphological traits with greater relevance for the early selection of cultivars with high yield potential. The experiment was installed in the northeast of São Paulo, Brazil. The experimental design used was randomized blocks with four replications. The treatments consisted of 17 dwarf Arabica coffee cultivars. There is variability among dwarf Arabica coffee cultivars for initial vegetative development. The growth and increase in the number of nodes of the plagiotropic branch can be used in early selection to identify cultivars with greater yield potential. The cultivars IAC Obatã 4739, Obatã IAC 1669-20, and Tupi IAC 1669-33 present higher initial vegetative performance in low-altitude environments. The results obtained are useful to breeders and producers for choosing the cultivars best adapted to cultivation in this environment.
Keywords: Coffea arabica L.; high temperatures; indirect selection; morphological traits; yield